2003
DOI: 10.1253/circj.67.768
|View full text |Cite
|
Sign up to set email alerts
|

Rescue Percutaneous Thrombectomy System Provides Better Angiographic Coronary Flow and Does Not Increase the In-Hospital Cost in Patients With Acute Myocardial Infarction

Abstract: In acute myocardial infarction (AMI), slow flow ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Although data based on large-scale surveys are insufficient in Japan, the length of hospital stay after AMI has been shown to be 3-6 weeks. [10][11][12][13][14] In the middle of the 1990s, the length of hospital stay after AMI was 4-6 weeks 10,11 and by the late 1990s, it was 3-4 weeks in AMI patients treated with PCI within 12 h or 24 h after onset. 12,13 In the present study, the mean length of hospital stay was 29.2 days in patients treated with PCI within 12 h of onset and 30.5 days in those treated within 24 h of onset.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although data based on large-scale surveys are insufficient in Japan, the length of hospital stay after AMI has been shown to be 3-6 weeks. [10][11][12][13][14] In the middle of the 1990s, the length of hospital stay after AMI was 4-6 weeks 10,11 and by the late 1990s, it was 3-4 weeks in AMI patients treated with PCI within 12 h or 24 h after onset. 12,13 In the present study, the mean length of hospital stay was 29.2 days in patients treated with PCI within 12 h of onset and 30.5 days in those treated within 24 h of onset.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14] In the middle of the 1990s, the length of hospital stay after AMI was 4-6 weeks 10,11 and by the late 1990s, it was 3-4 weeks in AMI patients treated with PCI within 12 h or 24 h after onset. 12,13 In the present study, the mean length of hospital stay was 29.2 days in patients treated with PCI within 12 h of onset and 30.5 days in those treated within 24 h of onset. Although the length of hospital stay seems to be longer than that in the previous studies, it is necessary to conduct a nation-wide survey to examine regional differences of the length of hospital stay after AMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now possible to aspirate coronary arterial thrombi using coronary arterial thrombectomy, [7][8][9] and to evaluate the pathological images in vivo. 10,11 So we investigated the characteristics of the pathological images of coronary arterial thrombi according to the infarct-related coronary artery.…”
mentioning
confidence: 99%
“…In contrast, although the length of hospital stay in Japan has gradually decreased, it is still extremely long, at approximately 4 weeks. [17][18][19][20][21][22] In a recent study, we showed that the length of hospital stay did not correspond appropriately to the severity of AMI. 22 These findings suggest that the hospital stay could be reduced without adverse effect for AMI patients in Japan.…”
mentioning
confidence: 99%